PENGARUH PERILAKU KONSUMEN TERHADAP MINAT BELI MERCHANDISE KPOP (Studi Pada Penggemar Kpop Di Kota Gorontalo) - Lolonto, Cynthia Dwi Cahyani; Isa, Ramlan Amir; Abdussamad, Zulfia K (Peneliti.net, 2024)
This research aimed to determine the influence of consumer behavior on the purchase interest of Kpop merchandise. This study was quantitative research. The population for this research consisted of Kpop fans in Gorontalo City. The sample size was 98 respondents. The research was measured using the slovin formula with a confidence level of 100%. Instrument testing involved validity and reliability assessments. The analysis technique employed was simple linier regression, and partial tests (t-tests) were used to the test the research hypotheses. The results of this research indicated that fans’ perception of consumer behavior has a positive influence on the purchase interest of Kpop merchandise. Consumer behavior towards Kpop merchandise is influenced by personal factors, where fans perceive Kpop merchandise as unique and cute items. This can be seen from the descriptive analysis of consumer behavior variables, with the highest average score being 4,31%. In this context, fans of Kpop merchandise believe that statements related to personal factors can echance their purchase interest in Kpop merchandise.